Transforming Learning Management through Virtual Learning Environments: A Multiple Case Study Approach - Eko Nurhaji Purnomo; Ainul Hayat (Universitas Negeri Padang, 2026)
The rapid advancement of digital technology has transformed the educational landscape, prompting institutions to rethink conventional learning management practices. The integration of Virtual Learning Environments (VLEs) has emerged as a strategic innovation that fosters inclusive, interactive, flexible, and learner centered education. This study adopts a qualitative multiple case study design to explore how VLE integration transforms learning management across three schools with distinct characteristics. The findings indicate that transformation occurs across three dimensions planning: shifting from traditional design to digitally integrated curriculum development, implementation: evolving from instructional teaching to facilitative digital engagement and evaluation: transitioning from manual assessment to adaptive digital analytics. Major challenges include teachers limited digital competence, low self efficacy, and resistance to pedagogical change. Continuous professional development and emotional readiness programs are essential to strengthen teachers’ capacity for technology integration. The qualitative scope and limited number of cases constrain the generalizability of the findings, as contextual and infrastructural variations may influence implementation. Future studies should broaden contextual coverage and employ mixed methods to enhance the validity and applicability of results. Theoretically, this study advances understanding of digital pedagogy transformation, while practically emphasizing the importance of teacher competence, robust infrastructure, and adaptive learning cultures in sustaining educational innovation.